2010
DOI: 10.1074/jbc.m109.098616
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-induced Apoptosis of Hypertrophic Chondrocytes Is Associated with a Decrease in Mitochondrial Membrane Potential and Is Dependent upon Erk1/2 Phosphorylation

Abstract: Growth plate abnormalities, associated with impaired hypertrophic chondrocyte apoptosis, are observed in humans and animals with abnormalities of vitamin D action and renal phosphate reabsorption. Low circulating phosphate levels impair hypertrophic chondrocyte apoptosis, whereas treatment of these cells with phosphate activates the mitochondrial apoptotic pathway. Because phosphate-mediated apoptosis of chondrocytes is differentiation-dependent, studies were performed to identify factors that contribute to hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
54
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 22 publications
9
54
0
1
Order By: Relevance
“…Acidemia, a condition associated with defective skeletal mineralization (17), was present in a substantial percentage of study participants; however, defective mineralization was equally prevalent in nonacidemic individuals, suggesting that acidemia did not affect the prevalence of abnormal mineralization in the current cohort. Moreover, levels of Consistent with the stimulatory actions of PTH on osteoblasts, circulating PTH levels were associated with increased osteoid accumulation in this study and, consistent with data from Hyp mice (35), phosphorus concentrations were consistently, independently, and inversely associated with both osteoid accumulation and osteoid maturation time. These findings suggest that altered phosphorus sensing or metabolism may be involved in the pathogenesis of the defective skeletal mineralization in pediatric CKD.…”
Section: Discussionsupporting
confidence: 88%
“…Acidemia, a condition associated with defective skeletal mineralization (17), was present in a substantial percentage of study participants; however, defective mineralization was equally prevalent in nonacidemic individuals, suggesting that acidemia did not affect the prevalence of abnormal mineralization in the current cohort. Moreover, levels of Consistent with the stimulatory actions of PTH on osteoblasts, circulating PTH levels were associated with increased osteoid accumulation in this study and, consistent with data from Hyp mice (35), phosphorus concentrations were consistently, independently, and inversely associated with both osteoid accumulation and osteoid maturation time. These findings suggest that altered phosphorus sensing or metabolism may be involved in the pathogenesis of the defective skeletal mineralization in pediatric CKD.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies from our and other laboratories have shown that ascorbic acid and additional 1.5 mM P i stimulated hypertrophic, terminal, and mineralization events of growth plate and sternal chondrocytes (11,15). Other studies showed that extracellular P i is transported back into chondrocytes via the Na ϩ /P i co-transporter where it acts as a signaling molecule that activates various signaling pathways, including the ERK-MAPK signaling pathway (23). In this study, we show that ascorbic acid and additional 1.5 mM P i activate PKC␣ and ultimately ERK and p38 MAPK signaling pathways.…”
Section: Discussionsupporting
confidence: 58%
“…Co-immunostaining with antibodies specific for type X collagen (hypertrophic marker) revealed that hypertrophic chondrocytes were equally well transfected as non-hypertrophic chondrocytes (data not shown). Cells were cultured in the absence or presence of 50 g/ml ascorbic acid and additional 1.5 mM inorganic phosphate (P i ), a myristoylated protein kinase C inhibitor [20][21][22][23][24][25][26][27][28]; specific PKC␣ inhibitor; 10 M; Calbiochem), PD98059 (specific ERK inhibitor; 10 M; Millipore, Billerica, MA), or SB203580 (specific p38 inhibitor; 10 M; Millipore). After 6 days of culture, cells were stained for APase activity using alkaline phosphatase magenta immunohistochemical substrate solution (Sigma), or APase activity was determined in cell lysates using p-nitrophenyl phosphate as a substrate as described previously (11).…”
Section: Methodsmentioning
confidence: 99%
“…GFP immunostaining suggested presence of both donor (52.49% -2.57%) and host cells (47.51% -2.57%) in the cartilaginous region (NS, not significant, p = 0.18), while bone tissue was thought to be completely host derived (E, F). differentiation, chondrocytes activate an apoptosis program as a result of phosphate stimuli and hence contribute to cartilage remodeling during EO (Miedlich et al, 2010). Surprisingly, higher levels of Runx2 were detected in iChon Con cells when compared to iChon Ind , whereas no collagen type X expression was detected.…”
Section: Fig 6 Scaffolds Seeded With Ichonmentioning
confidence: 93%
“…Despite absence of donor contribution to bone formation, we can conclude that iChon Ind cells are able to trigger EO. Indeed, the results that have been published on whether hypertrophic chondrocytes are able to transdifferentiate to osteoblasts during EO are conflicting (Miedlich et al, 2010;Roach, 1992). Moreover, it has previously been reported that hypertrophic chondrocytes activate an apoptosis program while expressing vascular endothelial growth factor to stimulate blood vessel ingrowth (Adams and Shapiro, 2002;Gerber et al, 1999).…”
Section: Fig 6 Scaffolds Seeded With Ichonmentioning
confidence: 99%